2019
DOI: 10.1111/and.13492
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the phytomodulatory potential of fenugreek ( Trigonella foenum‐graecum ) on bisphenol‐A induced testicular damage in mice

Abstract: Bisphenol A (BPA), an organic synthetic compound and endocrine disruptor, which majorly cause deleterious effects on male reproductory system. Fenugreek (Trigonella foenum-graecum), associated with Leguminosae family is used as a herbal medicine with potent antioxidant properties. The present study was aimed to scrutinise the preventative role of fenugreek seeds aqueous extract (FSEt) on BPA-induced testicular damage in mice. Study included four different groups of male Balb/c mice: contol (C), fenugreek (FSEt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…BPA disrupts spermatogenesis by inhibiting androgen production and reducing Sertoli cell number and function [ 30 , 81 , 82 , 83 , 84 ]. Furthermore, BPA exposure decreased the seminiferous tubule diameters and increased tubule atrophy and damage [ 26 , 27 , 85 , 86 , 87 ], induced germinal cell debris and congestion [ 27 , 86 , 88 ], as well as induced the reduction and/or degeneration of spermatocytes [ 25 , 27 , 32 , 89 , 90 ] and other spermatogenic cells [ 22 , 26 , 30 , 86 , 87 , 89 , 90 ]. A recent study in mice showed that chronic exposure to BPA impairs the proliferation of spermatogonia and spermatocytes, resulting in poor sperm quality, especially reduced sperm counts and motility [ 91 ].…”
Section: Bpa-induced Alterations In Testicular Structure Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…BPA disrupts spermatogenesis by inhibiting androgen production and reducing Sertoli cell number and function [ 30 , 81 , 82 , 83 , 84 ]. Furthermore, BPA exposure decreased the seminiferous tubule diameters and increased tubule atrophy and damage [ 26 , 27 , 85 , 86 , 87 ], induced germinal cell debris and congestion [ 27 , 86 , 88 ], as well as induced the reduction and/or degeneration of spermatocytes [ 25 , 27 , 32 , 89 , 90 ] and other spermatogenic cells [ 22 , 26 , 30 , 86 , 87 , 89 , 90 ]. A recent study in mice showed that chronic exposure to BPA impairs the proliferation of spermatogonia and spermatocytes, resulting in poor sperm quality, especially reduced sperm counts and motility [ 91 ].…”
Section: Bpa-induced Alterations In Testicular Structure Functionmentioning
confidence: 99%
“…Recently, several phytochemicals [ 88 , 89 ] and plant extracts [ 30 , 31 , 32 , 90 ] showed an ameliorative effect on testicular function and semen quality in human and animal models exposed to BPA. Cordyceps militaris , a medicinal fungus widely used in traditional Chinese medicine, contains many active components, such as cordycepin, polysaccharides, and cordycepin acid, with anti-bacterial, anti-tumour and anti-oxidative properties [ 139 ].…”
Section: Ameliorative Effects Of Antioxidants In Bpa-induced Repromentioning
confidence: 99%
See 1 more Smart Citation
“…A significant decline in the activities of SOD, CAT and GSH/GSSG ratio, whereas a noticeable increase in the GST activity was observed in the BPA‐induced mice when compared to control mice, which showed toxic effects (increasing the OS) of BPA on the mice testis . Previously published reports also evidenced the BPA‐incited toxicity via disrupting the antioxidant defence system and excess ROS generation (Kaur & Sadwal, 2020; Kaur et al., 2018, 2020). However, Se supplementation restored the activities of all these in Se co‐treated group, presenting its role in eliminating free radicals, and this might be the fundamental compensatory mechanism to avoid the development of the OS.…”
Section: Discussionmentioning
confidence: 90%
“…It has been stated that BPA exposure induced the oxidative stress (OS) within body and interfere with the function of androgen receptors and male sex hormones by inducing excessive free radicals (Manfo et al., 2014). The OS created by free radicals can cause severe damage to vital components of the cell and also deregulate the inherent repair mechanism, which ultimately leads to cell apoptosis (Kaur & Sadwal, 2020; Kaur et al., 2020). Adverse consequences of BPA exposure on spermatogenesis comprise a marked decline in the weight of prostate and testes, and decreased thickness as well as diameter of seminiferous tubules (Kaur et al., 2020; Qiu et al., 2013).…”
Section: Introductionmentioning
confidence: 99%